Managing public services innovation : the experience of English housing associations - Walker, Richard M.; Jeanes, Emma.; Rowlands, Robert (Bristol : Policy Press, 2001)
Managing public services innovation provides the first in-depth exploration of innovation and the management of innovation in the housing association sector. Drawing on longitudinal case studies and data sets, including the Housing Corporation's Innovation and Good Practice database, it explores techniques to develop evidence-based policy in the housing association sector, and makes recommendations for best practice.
MANAGING PUBLIC SERVICES INNOVATION; Contents; List of tables, figures and boxes; Acknowledgements; Summary; 1. Introduction; 2. Public services innovation:perspectives on innovation in organisation and management; 3. The housing association policy environment, regulation and innovation; 4. Classifying and measuring innovation; 5. In search of the innovative housing association; 6. Managing innovation; 7. Conclusions; References; Index.
Includes bibliographical references (pages 111-119) and index.
Print version record.
JSTOR
Keywords: Housing -- England -- Societies, etc; Housing management -- England; Logement -- Gestion -- Angleterre; BUSINESS & ECONOMICS -- Economics -- General; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; Housing management; Housing -- Societies, etc; England